2011
DOI: 10.1073/pnas.1115749108
|View full text |Cite
|
Sign up to set email alerts
|

Covalent modification of reduced flavin mononucleotide in type-2 isopentenyl diphosphate isomerase by active-site-directed inhibitors

Abstract: Evidence for an unusual catalysis of protonation/deprotonation by a reduced flavin mononucleotide cofactor is presented for type-2 isopentenyl diphosphate isomerase (IDI-2), which catalyzes isomerization of the two fundamental building blocks of isoprenoid biosynthesis, isopentenyl diphosphate and dimethylallyl diphosphate. The covalent adducts formed between irreversible mechanismbased inhibitors, 3-methylene-4-penten-1-yl diphosphate or 3-oxiranyl-3-buten-1-yl diphosphate, and the flavin cofactor were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 29 publications
9
34
0
Order By: Relevance
“…Therefore, revealing the electron density in the N-terminal region of the new structure is thought to be a result of improvement of the crystal quality and the resolution. Moreover, the orientation and conformation of the N-terminal region in the new structure distinctly differ from those of the previously reported substratecomplex structures (22,33), in which the N-terminal region forms an ␣-helix to construct a part of the substrate-binding site. A superimposed structure of the type 2 IDI-FMN-IPP ternary complex in the reduced state (PDB code 3B05) showed that the N-terminal ␣-helix in the new structure partially unwinds to interact with the ␣-helix (␣11=) and loop regions between ␣11= and ␣12= in the neighboring tetramer unit (Fig.…”
Section: Resultsmentioning
confidence: 52%
See 4 more Smart Citations
“…Therefore, revealing the electron density in the N-terminal region of the new structure is thought to be a result of improvement of the crystal quality and the resolution. Moreover, the orientation and conformation of the N-terminal region in the new structure distinctly differ from those of the previously reported substratecomplex structures (22,33), in which the N-terminal region forms an ␣-helix to construct a part of the substrate-binding site. A superimposed structure of the type 2 IDI-FMN-IPP ternary complex in the reduced state (PDB code 3B05) showed that the N-terminal ␣-helix in the new structure partially unwinds to interact with the ␣-helix (␣11=) and loop regions between ␣11= and ␣12= in the neighboring tetramer unit (Fig.…”
Section: Resultsmentioning
confidence: 52%
“…As a result, we succeeded in solving the new structure of S. shibatae type 2 IDI at a resolution of 1.7 Å, which is the highest level yet obtained (Table 1, PDB code 3VKJ). Although the new structure contained no electron density of NADH, a remarkable difference between the new and the previously reported structures (22,33) was found in the N-terminal region (Fig. 1A and B).…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations